An experimental and computational study of OH formation in laminar coflow syngas diffusion flames. (1st August 2018) - Xu, Huanhuan; Sun, Shaozeng; Liu, Fengshan; Zhao, Yijun; Liu, Yuying; Chen, Lei; Meng, Shun
Abstract: This paper presents an experimental and numerical study to elucidate the suppressing influence of H2 content in syngas on OH formation in laminar syngas diffusion flames burning in coflow oxidizer of 25%O2 /75%H2 O. Such an influence was found different from the effect of H2 content in syngas on OH formation when the oxidizer stream consists of O2 /N2 . OH ∗ -chemiluminescence images were captured using an intensified CCD (ICCD) camera, the centerline temperatures were measured by a Pt-6%Rh/Pt-30%Rh thermocouple, while a two-dimensional flame code was adopted to simulate these laminar coflow diffusion flames using a detailed reaction mechanism. The different effects of H2 O including chemical, thermal, transport, and radiative were examined and detailed kinetics analyses were conducted to gain insights into how H2 O in the oxidizer stream alters the influence of H2 content in syngas on OH formation.